Research on Screening Method of Loess Slope Stability Evaluation Indexes Based on Validity and Reliability Coefficient - Jianlong Liao; Hongjun Sun; Jianchao An (Applied Sciences)
Aiming at the problems of intense subjectivity and high redundancy in the screening of indicators in the stability evaluation of loess slopes, this study proposes an evaluation method integrating the validity and reliability coefficients. Following an initial screening of the indexes based on the engineering geological characteristics of loess slopes and literature research, 22 significant indicators were kept following a qualitative screening process (the principles of uniqueness, purpose, etc.); combined with the improved grey correlation-Delphi model for quantitative screening, the validity coefficient (<semantics>β=0.0816</semantics>) and reliability coefficient (<semantics>ρ=0.9609</semantics>) were introduced to validate the scientificity and consistency of the indicator system. The results showed that the 10 core indicators, including Cohesion, Internal Friction Angle, Maximum Monthly Rainfall, Rock Mass Structure, and Anthropogenic Engineering Activities, had a significant influence on loess slope stability, and the screening process effectively reduced the subjective bias and information redundancy. The method provides a data-driven theoretical framework for eolian slope risk assessment, which can improve the accuracy of landslide warning and the reliability of engineering protection design, and the engineering applicability of the model can be further optimized by combining the dynamic environmental parameters and multi-source monitoring data.